IN VITRO ANTIBACTERIAL ACTIVITY OF CARICA PAPAYA LEAF EXTRACT-LOADED ACNE PATCHES AGAINST Propionibacterium acnes - Indriaty, Sulistiorini; Rizikiyan, Yayan; Gianto, Vinie Regina Putri; Karlina, Nina; Hidayati, Nur Rahmi; Sulastri, Lela; Firmansyah, Deni (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2025)
Acne vulgaris is a prevalent skin condition that is characterized by inflammatory lesions. Propionibacterium acnes is a key bacterium implicated in its pathogenesis. This study aimed to investigate the antibacterial potential of Carica papaya leaf extract against P. acnes and its efficacy when formulated into acne patches. Ethanolic extracts of C. papaya leaves were prepared at concentrations of 20%, 25%, and 30%. These extracts were incorporated into acne patch formulations and evaluated for antibacterial activity using the paper disc diffusion method. Clindamycin 1% was used as a positive control and 70% ethanol was used as a negative control. The results demonstrated that all concentrations of the C. papaya leaf extract exhibited significant antibacterial activity against P. acnes. The 30% concentration demonstrated the largest zone of inhibition, which was comparable to that of the positive control. These findings suggest that C. papaya leaf extract-based acne patches are promising natural alternatives for the treatment of acne vulgaris. Keywords: Papaya leaves (Carica papaya L), Propionibacterium acne, Acne patch, Inhibitory power